Digital inclusion policies in a high Andean Quechua region of Peru - Mescua Figueroa, Augusto César; Vértiz-Osores, Ricardo Ivan; Mendoza Torres, Christian Paulina; Peceros Mescua, Keith Eduardo (CIENCIA ergo-sum, 2024)
Internet connectivity has become a fundamental right today. The study was aimed at evaluating digital inclusion policies in a Quechua-speaking region of Peru from a qualitative case study approach. Education specialists and regular basic education principals participated through semi-structured interviews. The lack of technological infrastructure for internet access and weak connectivity, which affects teachers’ digital literacy and students’ learning, were highlighted. It is concluded that internet access is not sufficient to meet the criteria for implementing digital inclusion policies. It is recommended to increase and strengthen the training of teachers in digital skills.